2016
DOI: 10.1007/s11356-016-6475-x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of quinolone antibiotic, norfloxacin, in aqueous solution using gamma-ray irradiation

Abstract: This study reports the efficiency of gamma-ray irradiation to degrade quinolone antibiotic, norfloxacin, in aqueous solution. Laboratory batch experiments were conducted to determine the "pseudo-first" order degradation kinetics of norfloxacin in the concentration ranges of 3.4-16.1 mg L(-1) by gamma-ray irradiation. The dose constant was found to be dependent on the initial concentration of norfloxacin and gamma-ray irradiation dose rate (D r). The saturation of norfloxacin sample solutions with N2, air or N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(22 citation statements)
references
References 46 publications
1
17
0
4
Order By: Relevance
“…Furthermore, the colored form of MB cannot be biodegraded more easily as compared to its reduced colorless form. Several methods have been designed for the removal of MB and other organic pollutants from waste water such as adsorption desorption strategy [3][4][5][6], c-irradiation [7], ozonation [8][9][10], photocatalysis [11][12][13], ion exchange [14], membrane separation [2], reverse or forward osmosis [15], electrochemical methods [16,17], biochemical materials [18][19][20], but all these methods are either very expensive or cannot remove the pollutants completely. Chemical reduction method used to convert these dyes from toxic state to nontoxic or less toxic form is very easy and environmentally friendly, but the reduction of these dyes without catalyst takes much time.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the colored form of MB cannot be biodegraded more easily as compared to its reduced colorless form. Several methods have been designed for the removal of MB and other organic pollutants from waste water such as adsorption desorption strategy [3][4][5][6], c-irradiation [7], ozonation [8][9][10], photocatalysis [11][12][13], ion exchange [14], membrane separation [2], reverse or forward osmosis [15], electrochemical methods [16,17], biochemical materials [18][19][20], but all these methods are either very expensive or cannot remove the pollutants completely. Chemical reduction method used to convert these dyes from toxic state to nontoxic or less toxic form is very easy and environmentally friendly, but the reduction of these dyes without catalyst takes much time.…”
Section: Introductionmentioning
confidence: 99%
“…Higher% degradation of diclofenac at pH 6.68-8 is probably due to higher concentration of OH radicals and O 2 À ions in the solution at this pH [25]. The decrease in% degradation at pH 11 may be due to the fact that H radical can react with OHÀ À to generate e aq À and thus increasing the concentration of e aq À [4]. These increased e aq À then reacts with OH radicals by inter-radical recombination reactions (Eq.…”
Section: Effect Of Solution Ph On Degradation Of Diclofenacmentioning
confidence: 98%
“…The worldwide annual production of pharmaceuticals is in thousands of tons which can cause harmful effects in terrestrial as well as in aquatic ecosystems [2,3]. The use of pharmaceuticals has serious consequences because most of them are persistent, bio accumulative and have long range transportable behaviour in the ecosystem [4]. The presence of pharmaceuticals in water indicated their inefficient removal by outdated traditional water purification techniques, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that removal of NOR by conventional water treatment techniques cannot effectively remove it from aqueous solution because of its aromatic nature. Thus, its existence can cause serious health issues through contaminating drinking water …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the holes caused in the valence band due to reaction with H 2 O on the surface of the catalyst make hydroxyl radicals. The hydroxyl radicals formed are the principal agents for the oxidation of NOR to transform it into by‐products at optimum time and finally to simple non‐polluting compounds at longer time …”
Section: Introductionmentioning
confidence: 99%